The Influence of Electronic Word of Mouth, Product Quality, and Promotion on the Decision to Purchase Casablanca Deodorant in Batam (International Journal of Economics and Management Research, 2026)
This study aims to determine the influence of electronic word of mouth, product quality, and promotion on the decision to purchase Casablanca deodorant in Batam. This study is a quantitative study. The population in this study are users of Casablanca brand deodorant who have made purchases in the Sekupang District. The population used in this study does not have a definite number. Because the number of the population used in this study is unknown, the researcher used Jacob Cohen's formula of 204 respondents. The technique used in this study is non-probability sampling with purposive sampling. The researcher used a questionnaire with several questions to be answered by the respondents. Based on the hypothesis testing results, it is known that the electronic word of mouth variable has a t-value of 2,636 > 1,971 with a sign of 0,009 < 0,05. The product quality variable had a t-value of 6,028 > 1,971 with a sign of 0,000<0,05. The promotion variable had a t-value of 3,405 > 1,971 with a sign of 0,001<0,05. This is obtained from the f-calculated value of 83,314, which is greater than the f-table value of 2,65, with a significance level of 0,000, which is less than 0,05. Electronic word of mouth, product quality, and promotions have a positive and significant effect on purchasing decisions.